Integration of Computational Thinking in the Elementary School Curriculum: Teacher Perspectives and Experiences - Rati, Ni Wayan; Sudatha, I Gde Wawan; Dwiarwati, Kadek Ari; Lesmana, Kadek Yogi Parta (International Journal of Research in Counseling and Education, 2024)
With the increasing need for computational thinking skills in the digital era, it is important for basic education to start introducing this concept from an early age. This research aims to explore teachers' perspectives and experiences in integrating computational thinking (CT) into the elementary school curriculum. This research uses a mixed approach (mix method), data was collected through questionnaires and distributed to 130 teachers and using in-depth interviews with teachers in several elementary schools. The research results show that most teachers understand the importance of CT and feel that its integration can enrich the learning process. However, there are various challenges faced, including limited resources, lack of training, and resistance to curriculum change. Despite this, some teachers have successfully implemented CT in a variety of subjects through the use of problem-based projects and digital tools. This research concludes that greater support from schools and the provision of ongoing training is needed to optimize the integration of CT in the elementary school curriculum. It is hoped that these findings will provide insight for policy makers and educators to design more effective strategies in developing computational thinking skills at the basic education level.